Some Phonological Aspects of Vocoids and Contoids with Reference to English and Arabic Language - Sawsan A. Qasim (Mahesa Research Center, 2023)
This article investigates the most important dichotomy in phonology—the concept of vocoids and contoids. Pike (1943:66-78) proposed two separate distinctions, one strictly phonetic and the other based on function, or phonological criteria, as a possible solution to this terminology. Pike suggests the words vocoid and contoid for the phonetic distinction. The appropriateness of drawing a distinction based on the acoustics and articulation of sounds has been contested by a variety of linguists. In order to identify and analyze both the articulatory and acoustic aspects of a segment, most of phonologists claim that it is important to separate vocoids and contoids. In terms of acoustics and articulation, all sounds in the world's languages can be roughly divided into vocoids and contoids. This study also compares certain phonological aspects between English and standard Arabic related to the previous mentioned terms to show the similarities and differences between the two languages.